Prioritizing the dimension of resilient deteriorated urban fabric based on a disaster resilience of place model (case study: the deteriorated urban fabric of Karaj) - mahsa asadi aziz abadi; keramat alah ziari; mohsen vatan khahi (تحقیقات کاربردی علوم جغرافیایی)
A city is a vibrant, dynamic, and evolving phenomenon that grows and spreads over time and space, and is exhausted and degraded.It also faces crises such as natural hazards and artifacts, resulting from human relationships and physical elements, on the one hand, and social, economic, cultural, geographical, political, and historical conditions on the other. The deteriorated urban fabric, which has physical, functional and operational deterioration, are resistant to the above-mentioned crises and has low vulnerability. Therefore, the need of intervening in these fabrics is crucial for balancing, coordinating the foundations of social life, and improving the urban structure. In this regard, in this research, priority is given to the dimension of resilient deteriorated urban fabric based on a disaster resilience of place model which is one of the models of urban resilience measurement. This research is a descriptive-analytical according to method and is developmental-applied research in terms of the purpose. Also, Expert Choice software and AHP model are used to analyze the collected data by using a questionnaire. The results of the research indicate that, in three macro areas of Karaj, Hesarak and Mehrshahr, the physical-environmental resilience dimension has the highest weight and organizational-institutional resilience has the least weight. Overall, regarding prioritization of resilience dimensions, criteria and indicators, an increasing per capita of vital use in study areas, changing the economic structure of residents, as well as increasing the skill and coherence of citizens to deal with hazards and crises are important.